OPTIMALISASI IMPLEMENTASI KOMPILASI HUKUM ISLAM DALAM KASUS PERCERAIAN, NAFKAH, DAN HAK ANAK: TANTANGAN DAN RELEVANSI DENGAN MAQASHID SYARIAH - Sirojuddin, Mohammad; Hudi Hidayat; Nur Aula Yazid (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
The Compilation of Islamic Law has served as the primary reference for resolving family law cases in Indonesia’s religious courts, particularly those concerning divorce, alimony, and children's rights. However, its practical implementation still faces both structural and substantive challenges that affect the protection of vulnerable parties post-divorce and hinder the optimal realization of justice principles in judicial decisions. This study aims to analyze the obstacles in the implementation of the Compilation of Islamic Law in family cases and evaluate its relevance to the principles of Maqāṣid al-Sharīʿah as a normative approach that ensures public welfare (maṣlaḥah) and substantive justice. Employing a literature review method with a narrative approach, this research uses secondary data obtained from legal documents, academic journals, and religious court rulings, analyzed through content and thematic analysis techniques. The main findings reveal that the implementation of the Compilation of Islamic Law remains largely formalistic and does not fully reflect the core values of Maqāṣid al-Sharīʿah, such as the protection of life, lineage, and property. Furthermore, the absence of systematic integration of maqāṣid principles in judicial reasoning has led to inconsistencies in the application of maṣlaḥah-based justice, particularly in cases involving alimony and child custody. This article offers a theoretical contribution by reinforcing the conceptual framework of Maqāṣid al-Sharīʿah in the reformulation of Islamic family law in Indonesia, and provides strategic recommendations for strengthening legal norms and judicial practices that are more contextual and socially responsive.